Customer focus : a strategy for success - Langevin, Roger G. (Crisp management library ;, 1998)
As strategic concepts, customer driven quality and service have moved to the top of the list for most managers. A day does not go by without some reminder of how important these factors have become. The tools that this book uses to examine and develop these topics are both familiar and critical. Market research, quality systems and performance measures are an essential part of a sound strategy to deliver the best that can be achieved for any customer.